2009
DOI: 10.1002/ijc.24216
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ezrin in the growth and invasiveness of esophageal squamous carcinoma cells

Abstract: Ezrin, which crosslinks the cytoskeleton and plasma membrane, is involved in the growth and metastatic potential of cancer cells. Ezrin expression in esophageal squamous cell carcinoma (ESCC) was described recently, but its roles and the underlying mechanism(s) remain unclear. In our study, we first showed that ezrin in ESCC cell is expressed in the nucleus as well as in the cytoplasm and plasma membrane. Then, by using RNAi, we revealed that interference of ezrin expression suppressed the growth, adhesion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 35 publications
9
68
0
2
Order By: Relevance
“…Ezrin is associated with malignant progression and metastasis in a variety of human malignancies (Chen et al, 2001;Weng et al, 2005;Sarrió et al, 2006;Deng et al, 2007;Mhawech-Fauceglia et al, 2007;Elzagheid et al, 2008;Xie et al, 2009;Morales et al, 2010;Wang et al, 2011). Ezrin shows high expression in epithelial cell resource tumors, such as esophageal squamous cell carcinoma (ESCC) (Xie et al, 2009), nasopharyngeal carcinoma (Wang et al, 2011), colorectal cancer (Elzagheid et al, 2008), and ovarian epithelial carcinoma (Mhawech-Fauceglia et al, 2007), which predicts poor prognosis in these tumors. Our results indicated that 75.0% (45/60) of LSCC and 84.8% (28/33) of metastatic lymph nodes showed increased expression of ezrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ezrin is associated with malignant progression and metastasis in a variety of human malignancies (Chen et al, 2001;Weng et al, 2005;Sarrió et al, 2006;Deng et al, 2007;Mhawech-Fauceglia et al, 2007;Elzagheid et al, 2008;Xie et al, 2009;Morales et al, 2010;Wang et al, 2011). Ezrin shows high expression in epithelial cell resource tumors, such as esophageal squamous cell carcinoma (ESCC) (Xie et al, 2009), nasopharyngeal carcinoma (Wang et al, 2011), colorectal cancer (Elzagheid et al, 2008), and ovarian epithelial carcinoma (Mhawech-Fauceglia et al, 2007), which predicts poor prognosis in these tumors. Our results indicated that 75.0% (45/60) of LSCC and 84.8% (28/33) of metastatic lymph nodes showed increased expression of ezrin.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin is involved in L1 (cell-neural adhesion molecule-mediated activation of nuclear factor kappa B signaling, which is a major route of progression in colorectal cancer (Gavert et al, 2010). Ezrin may influence the growth and invasiveness of ESCC cells through the mitogen-activated protein kinase and transforming growth factor-b pathways or by affecting the expression of certain cell proliferation-or invasiveness-related genes, such as ATF3, CTGF, or CYR61 (Xie et al, 2009). In human gastric carcinoma SGC-7901 cells, ezrin, radixin, or moesin were knocked down by small interfering RNA, which reduced cell migration and invasion by upregulating expression of E-cadherin (Ou-Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockdown of Ezrin expression by RNA interference leads to suppression of growth, adhesion and invasiveness of ESCC cells in vitro, and tumorigenicity in nude mice also reveals that Ezrin regulates tumor formation in vivo [10]. Furthermore, mRNA expression profiling was obtained using Affymetrix GeneChip Human genome U133 plus 2.0 and indicated that certain proliferation-and invasiveness-related genes are involved in Ezrin function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mRNA expression profiling was obtained using Affymetrix GeneChip Human genome U133 plus 2.0 and indicated that certain proliferation-and invasiveness-related genes are involved in Ezrin function [10]. However, the biological meaning of this mRNA profile is not fully understood.…”
Section: Introductionmentioning
confidence: 99%